Expression of miRNA‐371a‐3p in seminal plasma and ejaculate is associated with sperm concentration. (16th July 2019) - Radtke, A.; Dieckmann, K.‐P.; Grobelny, F.; Salzbrunn, A.; Oing, C.; Schulze, W.; Belge, G.
Abstract: Background: The microRNAs of the miR‐371‐3 cluster are novel serum markers for testicular germ cell tumors. Sporadic reports suggested the expression of this miRNA in semen. Objectives: To verify the expression of miR‐371a‐3p in seminal plasma and unprocessed ejaculate; to compare seminal plasma miRNA levels in germ cell tumors patients with those of controls; to look for an association of miRNA levels with semen quality. Materials and methods: The miR‐371a‐3p expression was analyzed with qPCR. The study population consisted of 100 participants: seminal plasma samples from 20 germ cell tumors patients and 30 controls, serum samples from 12 healthy men, ejaculate samples from 38 men undergoing fertility testing. Results: The seminal plasma miR‐371a‐3p levels of germ cell tumors patients were not different from controls. The miRNA expression was very low in serum but much higher in seminal plasma. In ejaculate samples, the miRNA expression significantly correlated with sperm concentration and the total sperm count. Discussion: miR‐371‐a‐3p is present in sperm‐containing fluids. Seminal plasma levels cannot be used to distinguish germ cell tumors from controls. The correlation with sperm concentration in ejaculate samples suggests the spermatozoa as possible source of miR‐371a‐3p production. Conclusion: The miR‐371a‐3p levels in ejaculate could represent a novel biomarker for the non‐invasive evaluation of male infertility.